Toxoplasmosis and Its Potential Role to Change the Levels of C - reactive protein and Vitamin D3 in Atherosclerosis Patients - Musa, Israa Salim; Saheb, Entsar Jabbar; Kuba, Rasha Hussain (Iraqi Journal of Science, 2021)
Atherosclerosis is a condition of the hardening of a blood vessel via the development of plaques around the artery wall which causes the artery to narrow, leading to severe complications. Toxoplasmosis is an opportunistic parasitic infection that causes pathological complications in immunocompromised patients, which lead to increase the burden on the immune system in these patients. This study aims to assess the incidence rate of toxoplasmosis in atherosclerosis patients and its potential to change C - reactive protein (C-RP) and vitamin D3 levels. Serum samples (150) were tested for the positivity of anti-Toxoplasma IgG and IgM antibodies by means of Enzyme-linked immunosorbent assay (ELISA). In addition, C-RP was assessed in all serum samples by means of Latex Fixation Test, while VtD3 was estimated by MiniVidas device. The results revealed that the seroprevalence of toxoplasmosis in atherosclerotic patients was comparatively higher as compared to that in the control group, with significant differences in C-RP and VtD3 levels. These results suggest that the decreased levels of VD3 lead to increase the incidence of T. gondii infection in atherosclerosis patients.